Influence of Static VAR Compensator for Undervoltage Load Shedding to Avoid Voltage Instability - Reshma Rajan; Venkateswara Rao; G. V. Nagesh Kumar (International Journal of Applied Power Engineering (IJAPE), 2014)
In the recent years, operation of power systems at lower stability margins has increased the importance of system protection methods that protect the system stability against various disturbances. Among these methods, the load shedding serves as an effective and last-resort tool to prevent system frequency/voltage instability. The analysis of recent blackouts suggests that voltage collapse and voltage-related problems are also important concerns in maintaining system stability. For this reason, voltage also needs to be taken into account in load shedding schemes. This paper considers both parameters in designing a load shedding scheme to determine the amount of load to be shed and its appropriate location .The amount of load to be shed from each bus is decided using the fixed step size method and it’s location has been identified by using voltage collapse proximity index method.  SVC is shunt connected FACTS device used to improve the voltage profile of the system. In this paper impact of SVC on load shedding for IEEE 14 bus system has been presented and analyzed.